The Dynamics of Gender: A Grassroots Perspective on Economic Resilience and Empowerment of the Tonga People in Kariba - Monica Monga; Munyaradzi A Dzvimbo; Tinashe M Mashizha (Budapest International Research and Critics University, 2019)
This paper examines the dynamics of gender-differentiated effects of economic resilience on rural livelihoods and infrastructure improvements of the Tonga people who predominantly resides in North Western Zimbabwe. The paper interrogates men and women’s empowerment as well as their roles of transforming their lives through engaging in various economic activities and infrastructural development in Mola, Nyaminyami District, Zimbabwe. This study uses a qualitative research approach which is backed by both primary and secondary data collection methods which are underpinned by mixed methods approach involving observation, focus group discussions with community members and in-depth interviews with community leaders and key stakeholders. The study proffers that while economic resilience affects both men and women, it disproportionately affects the amount of work women have to do which has a profound bearing on their ability to innovate and transform their obsolete infrastructure at their disposal. Hence, the study recommends ways to foreground gender mainstreaming in order to address emerging gender related challenges emanating from stereotyping and prejudice, stakeholder engagement and partnerships in revamping existing infrastructure.